Dendritic Cells and T Cells, Partners in Atherogenesis and the Translating Road Ahead - Sun, Li; Zhang, Wenjie; Zhao, Yanfang; Wang, Fengge; Liu, Shan; Liu, Lei; Zhao, Lin; Lu, Wei; Li, Minghui; Xu, Yuekang (Frontiers in Immunology, 2020)
Atherosclerosis is a chronic process associated with the arterial inflammation, accumulation of lipids, plaque formation in the vessel walls, and thrombosis with late mortal complications such as myocardial infarction and ischemic stroke. Immune and inflammatory responses have significant effects on every phase of atherosclerosis. Increasing evidences have showed that both innate and adaptive “arms” of the immune system play important roles in regulating the progression of atherosclerosis. A growing literature suggests that specialized innate immune cells called dendritic cells (DCs) play a key role as central orchestrators, whereas adaptive immune cells called T lymphocytes are crucial as active executors of the DC immunity in atherogenesis. These two important immune cell types work in pairs to establish pro-atherogenic or atheroprotective immune responses in vascular tissues. Therefore, understanding the role of DCs and T cells in atherosclerosis is extremely important. Here, in this review, we will present a complete overview, based on existing knowledge, of these two cell types in the atherosclerotic microenvironment and discuss the novel approaches of targeting DCs and T cells as a therapeutic strategy for the treatment of atherosclerosis.